The Implementation of Think Pair Share (TPS) Learning Model toward Student Achievement Learning in Material Acid and Base in Grade XI MA Sunan Pandanaran Academic Year 2018/2019 - Nafisa Rahmah; Krisna Merdekawati; Artina Diniaty (Universitas Islam Indonesia, 2019)
The purpose of this study was to determine the significant difference in student achievement learning through the implementation of a think pair share (TPS) learning model and conventional learning model on acid-base material. This research is an experimental study using quasi-experimental design, namely posttest only with nonequivalent group design. The study population was all students of class XI MA Sunan Pandanaran Yogyakarta academic year 2018/2019. The sample in this study was taken by purposive sampling technique as many as two classes. Data collection using the written test method with instruments in the form of multiple-choice questions to obtain data on learning achievement. Data analysis techniques in this study used Mann Whitney Test. Based on the results of the study it can be concluded that there are significant differences in learning achievement between students who take part in the TPS learning model and students who take the conventional model learning on acid-base material.